Kesuaman: Bahaya Laten terhadap Kehidupan Gereja Tuhan - Stephanus Hartoyo (SANCTUM DOMINE: JURNAL TEOLOGI, 2017)
Lukewarmness is a latent, serius and contagious spriritual sickness that keeps happening in a regularly repeated order— a cycle in the life of the believers in God as well as the Church. The Bible has all the records about it. The life of the Israelites and even the Church of Christ in its history, portray vividly how lukewarmness had been taking place over and over again. The world with all its attractions has dazzled the eyes of the Christians, so they focus and run for wealth and depise their spiritual needs. When their lives are care free, and complacent, they do not have time for God, or for the Church, and eventually, the church disappeares. The answer to the above condition is to do discipleship ministry consistently to the Christians so they become Christ-like disciples, freed from biblical illiteracy, and the lost of spiritual vitality. Christianity is not just a matter of confession, but a way of life in any situation, a full devotion to God.